PENGARUH LINGKUNGAN KERJA, KOMPENSASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PADA PT XYZ - Joni Efendi (JURNAL MITRA MANAJEMEN, 2021)
ABSTRACTThis study is a study to determine the effect of work environment, compensation, and work discipline on employee productivity at PT XYZ, using saturated sampling, as many as 64 employees, using qualitative data types that are quantified by literature study and questionnaires processed using a linkert scale. Data analysis using SPSS 26.0 obtained regression results of the magnitude of the influence of the work environment on employee productivity obtained tcount greater than ttable (6.352>1.999). The results of the regression of the magnitude of the effect of compensation on employee productivity showed that tcount> ttable (6.492>1.999). The results of the regression of the magnitude of the effect of work discipline on employee productivity showed that tcount> ttable (4.662>1.999), thus partially the work environment, compensation, and work discipline affected the productivity of PT XYZ employees. The result of Multiple Regression Y =14.076+〖0.756X〗_1+0.921X_2+〖0.688X〗_3, shows that the magnitude of the influence of the work environment, the magnitude of the effect of compensation, and the magnitude of the influence of work discipline with a value of a (constant) of 14.076, indicates that Fcount >Ftable (14,980>2,758). Thus, there is a simultaneous effect of the work environment, compensation, and work discipline on the productivity of PT XYZ's employees. Keywords: work environment, compensation, work discipline, employee productivity